Information effects of US monetary policy announcements on emerging economies: Evidence from Mexico - Carlos Alba; Julio A. Carrillo; Raúl Ibarra-Ramírez (Banco de México, 2024)
This paper analyzes, using a VAR model, the effects of US central bank monetary policy announcements, and information shocks from this authority regarding its economic outlook on Mexican financial and macroeconomic variables. Shocks are identified by combining a high-frequency strategy with sign restrictions, which exploits the co-movement between the policy rate and the stock market in the US around FOMC announcements. A restrictive monetary policy shock in the US is identified by an increase in the interest rate and a drop in stock prices, while a positive information shock is identified when both variables rise simultaneously. The results show that positive information shocks from the US central bank improve financial conditions in Mexico, appreciate the peso/dollar exchange rate, lower the sovereign risk premium and forex volatility, and increase stock prices, real activity and prices in Mexico. In contrast, restrictive US monetary policy shocks tighten financial conditions, and reduce real activity and prices in Mexico.
Keywords: E43; E52; E58; F42; 330; Monetary policy; international policy transmission; high-frequency identification; central bank information; VAR model